2018
DOI: 10.1007/s13365-018-0634-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural connectome differences in HIV infection: brain network segregation associated with nadir CD4 cell count

Abstract: This study investigated structural brain organization using diffusion tensor imaging (DTI) in 35 HIV-positive and 35 HIV-negative individuals. We used global and nodal graph theory metrics to investigate whether HIV was associated with differences in brain network organization based on fractional anisotropy (FA) and mean diffusivity (MD). Participants also completed a comprehensive neuropsychological testing battery. For global network metrics, HIV-positive individuals displayed a lower FA clustering coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 74 publications
1
19
1
Order By: Relevance
“…We suggest that this may be due to the small sample size which might be considered a limitation of the current study. Future studies will explore the data in multiple dimensions measuring topological properties using graph theoretical methods ( Abidin et al, 2018 ; Bell et al, 2018 ; Thomas et al, 2015 ) and evaluate the effect of working memory training on neurocognitive performance of HIV patients. The present study did not observe any significant correlations of age with ALFF and FC in either HIV+ or HIV- participants and there was no interaction effect between HIV and aging, suggesting that HIV may not have an age related neurodegeneration effect.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that this may be due to the small sample size which might be considered a limitation of the current study. Future studies will explore the data in multiple dimensions measuring topological properties using graph theoretical methods ( Abidin et al, 2018 ; Bell et al, 2018 ; Thomas et al, 2015 ) and evaluate the effect of working memory training on neurocognitive performance of HIV patients. The present study did not observe any significant correlations of age with ALFF and FC in either HIV+ or HIV- participants and there was no interaction effect between HIV and aging, suggesting that HIV may not have an age related neurodegeneration effect.…”
Section: Discussionmentioning
confidence: 99%
“…We and others did not find significant topology difference in structural network of HIV infected individuals (Samboju et al, 2018; Zhuang et al, 2017). However, two studies (Baker et al, 2017; Bell et al, 2018) have shown disrupted structural networks in HIV‐infected subjects compared to HC in terms of reduced global clustering coefficient, global network efficiency, and connection strength. These two studies differ from our study in the population enrolled.…”
Section: Discussionmentioning
confidence: 99%
“…Both FA and MD abnormalities have been previously reported in HIV‐infected subjects (Stebbins et al, 2007; Underwood et al, 2017; Zhu et al, 2013). Graph theoretical analysis of structural and functional connectome has also been used to show brain network topological changes in HIV‐infection (Abidin et al, 2018; Bell et al, 2018; Chockanathan, AM, Abidin, Schifitto, & Wismuller, 2018; Thomas, Brier, Ortega, Benzinger, & Ances, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We and others did not find significant topology difference in structural network of HIV infected individuals (Samboju, Philippi, Chan, Cobigo, Fletcher, Robb, Hellmuth, Benjapornpong, Dumrongpisutikul, Pothisri, Paul, Ananworanich, Spudich, Valcour, Search, et al, 2018; Zhuang et al, 2017). However, two studies (Baker et al, 2017; Bell et al, 2018a) have shown disrupted structural networks in HIV-infected subjects compared to HC in terms of reduced global clustering coefficient, global network efficiency, and connection strength. These two studies differ from our study in the population enrolled.…”
Section: Discussionmentioning
confidence: 99%
“…Both FA and MD abnormalities have been previously reported in HIV-infected subjects (Stebbins et al, 2007; Underwood et al, 2017; Zhu et al, 2013). Graph theoretical analysis of structural and functional connectome has also been used to show brain network topological changes in HIV-infection (Abidin et al, 2018; Bell et al, 2018b; Chockanathan, AM, Abidin, Schifitto, & Wismuller, 2018; Thomas, Brier, Ortega, Benzinger, & Ances, 2015).…”
Section: Introductionmentioning
confidence: 99%